Pengaruh Kebisingan Mesin Terhadap Konsentrasi Siswa Teknik Pemesinan SMK Warga Surakarta - Navadha Luciandany; Maria Paskanita Widjanarti; Farhana Syahrotun Nisa Suratna (Journal of Applied Agriculture, Health, and Technology, 2024)
Noise became one form of environmental pollution that provided negative impacts on human health and comfort. One common source of noise in vocational high school environments, especially in engineering, was machine noise. Exposure to machine noise reduced students concentration. Based on preliminary survey data that was conducted at SMK Warga Surakarta, this study aimed to determine the effect of machine noise on the concentration of machining students at SMK Warga Surakarta. This study was an analytical observational research with a cross-sectional design. The purposive sampling technique was used to obtain 31 respondents from a total of 128 machining students in the XI grade at SMK Warga Surakarta. The research instrument that was used in this study was a sound level meter to measure operating machine noise and a grid concentration test to conduct concentration test measurements. The data analysis techniques that were used included univariate analysis and bivariate analysis with the marginal homoginity test to compare students concentration results before and after exposure to noise. The results of the marginal homogeneity test showed a significant effect (p-value = 0.000). There was a significant effect before and after exposure to noise.